(RETRACTED) Effect of Sarang Semut (Myrmecodia pendans) Herbal Drink with Cinnamon Powder Against Blood Glucose in Sprague Dawley Rats with Type 2 Diabetes Mellitus - Rulla Ullaya Nazhifah; Fathimah Fathimah; Hafidhotun Nabawiyah (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2021)
This article is retracted due to authors-editorial team's missunderstanding.